Transfer Functions In Hierarchical Production Planning. - Kamil, Anton Abdulbasah (2005)
In the production planning it is essential to determine simultaneously the production program, the lot sizes as well as sequencing and scheduling the batches: the plannning of the production program requires the knowledge of the available manufacturing capacities;these depend, however, on the set-up times determined by lot-sizing, and the idle times of machines induced by sequencing and scheduling.